Community and agriculture resilience audits in two Kansas City communities - Kohn, Dustin Richard (My University, 2026)
Due to natural disasters, COVID-19, and economic shifts, resilient agricultural food systems have become increasingly important to cities. Research examining the conditions that support resilient agricultural production systems is critical. Grassroots urban agriculture initiatives often arise to help mitigate the effects of these disturbances. The ability of local initiatives to absorb and manage shock relies upon access to various forms of capital, including human, social, financial, physical, and natural capital. Along with these forms of capital, governance and political infrastructure can greatly influence food system resilience. Food system resilience audit tools have increased in popularity as a way to evaluate a food system’s accessibility to capital as well as examine system gaps and strengths. Many food system audit tools have been created to assess food systems at different system levels for different stakeholder audiences. This project used the audit tool titled the Community and Agriculture Resilience Audit Tool (CARAT), developed by the North American Food Systems Network, to assess how the communities of Kansas City, Missouri, and Kansas City, Kansas, are utilizing the assets of their food system to achieve food system resilience. During this study, policies, practices, and programs relating to the urban food system were analyzed by using the 101 indicators from CARAT. To analyze these urban food system assets, the researchers conducted interviews and focus groups with key community stakeholders. In these interviews, specific indicators from CARAT were used as questions to gauge the implementation or lack thereof of policies, practices, and programs specifically relating to urban food systems within the two cities. Searches of publicly available websites were also conducted to examine each city’s zoning ordinances and codes. After data collection, the 101 indicators are then scored based on the CARAT scoring guidelines: does not apply (x), no (0), being considered (1), in place (2), and being implemented (3). The results revealed that both cities have more policies, practices, and programs related to the theme of Community Self-Reliance in Food that can be utilized to enhance urban food system resilience. The area of focus for improvements in the two food systems is in the theme of Food Sovereignty, as it was discovered to have a limited availability of policies, practices, and programs. These scores act as a baseline for the two cities’ food systems and highlight areas of strength and weakness to community stakeholders to help prioritize actions to enhance urban food system resilience.
Keywords: Urban food system; Resilience; Food system assessment; Community planning; Urban agriculture